2009
DOI: 10.1002/jssc.200800724
|View full text |Cite
|
Sign up to set email alerts
|

Application of 10‐ethyl‐acridine‐3‐sulfonyl chloride for HPLC determination of aliphatic amines in environmental water using fluorescence and APCI‐MS

Abstract: Original PaperApplication of 10-ethyl-acridine-3-sulfonyl chloride for HPLC determination of aliphatic amines in environmental water using fluorescence and APCI-MS A simple, sensitive method for the determination of aliphatic amines based on a sulfonylation reaction using 10-ethyl-acridine-3-sulfonyl chloride (EASC) as pre-column labeling reagent with fluorescence detection and APCI-MS identification has been developed. The labeled derivatives exhibited high stability and were enough to be efficiently analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 41 publications
(22 reference statements)
2
11
0
Order By: Relevance
“…The sensitivity attainable is comparable to or even better than that of reported methods that employ fluorescent derivatization coupled with CE-LIF [23,24], LC-APCI/MS [12][13][14][15][16][17][18][19][20] and other GC methods.…”
Section: Applicationsupporting
confidence: 59%
See 1 more Smart Citation
“…The sensitivity attainable is comparable to or even better than that of reported methods that employ fluorescent derivatization coupled with CE-LIF [23,24], LC-APCI/MS [12][13][14][15][16][17][18][19][20] and other GC methods.…”
Section: Applicationsupporting
confidence: 59%
“…Several reagents for the determination of aliphatic amines by LC with fluorescence detection and post-column online identification by atmospheric pressure chemical ionization mass spectrometry (APCI/MS) [12][13][14][15][16][17][18][19][20] and APCI/MS-MS [21] have been reported. Application of capillary electrophoresis (CE) with UV- [22] and laser-induced fluorescence detection (LIF) [23,24] was also reported for the analysis of SCAAs.…”
Section: Introductionmentioning
confidence: 99%
“…Water was purified on a Milli-Q system (Millipore, Bedford, MA). EASC was synthesized in our laboratory [24]. Other chemicals used were analytical grade from Jining Chemical Reagent (Shandong, China).…”
Section: Chemicalsmentioning
confidence: 99%
“…This reagent showed many advantages including (1) reaction with primary and secondary amino groups and aromatic primary amino groups in the presence of sodium borate buffer (pH 9.0) can be carried out at mild condition without pretreatment steps to remove excess of reagent; (2) EASC was stable both in crystal state and in solution in the dark, and the derivatives were stable at room temperature in acidic conditions (pH 6-7); (3) EASC contains nitrogen and carbonyl oxygen atoms in contraposition, resulting in intramolecular isomerization easily and making an improvement to the ionizable efficiency of EASC biogenic amine derivatives with ESI-MS in positive-ion detection mode [24]. To the best of our knowledge, this is the first time that EASC fluorescent probe was applied to determine biogenic amines.…”
Section: Introductionmentioning
confidence: 99%
“…7‐Chloro‐4‐nitrobenzo‐2‐oxa‐1,3‐diazole (Khalil, 2009) has been developed for the determination of primary and secondary amino compounds. Data reported previously indicated that the reagent itself underwent about 50% decomposition in methanol–water solution exposed to daylight within 25 min (You et al ., 2009a–c) and a large number of fluorescent components that eluted later than the derviative itself had been found. 2‐(9‐Fluorenyl)‐ethyl chloroformate (FMOC) (Jámbor A and Molnár‐Perl I, 2009), 1‐(9‐fluorenyl)‐ethyl chloroformate (Waldhier et al ., 2009) and 2‐(9‐anthryl)‐ethyl chloroformate (AEOC) (Faulkner et al ., 1991) reagents have also been developed for the derivatization of amino acids and peptides for chiral or non‐chiral separation in LC or CE.…”
Section: Introductionmentioning
confidence: 99%